Risk factors in the onset of neck/shoulder pain in a prospective study of workers in industrial and service companies. Issue 9 (22nd August 2003) - Andersen, J H; Kaergaard, A; Mikkelsen, S; Jensen, U F; Frost, P; Bonde, J P; Fallentin, N; Thomsen, J F
Abstract : Aims: To quantify the relative contribution of work related physical factors, psychosocial workplace factors, and individual factors and aspects of somatisation to the onset of neck/shoulder pain. Methods: Four year prospective cohort study of workers from industrial and service companies in Denmark. Participants were 3123 workers, previously enrolled in a cross sectional study, where objective measurement of physical workplace factors was used. Eligible participants were followed on three subsequent occasions with approximately one year intervals. Outcomes of interest were: new onset of neck/shoulder pain (symptom cases); and neck/shoulder pain with pressure tenderness in the muscles of the neck/shoulder region (clinical cases). Results: During follow up, 636 (14.1%) participants reported neck/shoulder pain of new onset; among these, 82 (1.7%) also had clinical signs of substantial muscle tenderness. High shoulder repetition was related to being a future symptom case, and a future clinical case. Repetition was strongly intercorrelated with other physical measures. High job demands were associated with future status as a symptom case, and as a clinical case. A high level of distress predicted subsequent neck/shoulder pain, and neck/shoulder pain with pressure tenderness. Conclusions: High levels of distress, and physical and psychosocial workplace factors are predictors of onset of pain in the neck and/or shoulders, particularly pain with pressure tenderness in the muscles.